A nomogram for one-year risk of death after hip fracture - Guo, Jiale; Shi, Liuyang; Shi, Kehai; Dai, Ru; Wang, Jian; Li, Yehai (Frontiers in Medicine, 2025)
BackgroundHip fractures are catastrophic events with a significant risk of mortality, making early identification of high-risk patients crucial. While previous studies have primarily focused on post-surgical mortality in hip fracture patients, less attention has been given to those who did not undergo surgery. This study aimed to develop a nomogram to predict 1-year mortality in older adults following hip fractures.MethodsPatients hospitalized with hip fractures at a university hospital between May 2016 and December 2021 were included. Participants were randomly divided into training and validation cohorts (70:30 ratio). After selecting key variables, the nomogram was constructed, and its performance was evaluated in both cohorts.ResultsA total of 619 patients were included, with 136 (21.97%) experiencing mortality within one year. LASSO regression was used to account for multicollinearity, selecting variables such as age, coronary heart disease, surgery, hemoglobin, aspartate transaminase, and blood urea nitrogen. The nomogram achieved AUCs of 0.83 (95% CI: 0.78–0.88) and 0.81 (95% CI: 0.73–0.89) in the training and validation cohorts, respectively, demonstrating excellent calibration and clinical utility.ConclusionThe nomogram effectively predict 1-year mortality risk in older adults following hip fractures.